(untitled) (Research, Society and Development, 2022)
Competitiveness challenges lead companies to restructure their growth strategies, seeking consolidation in certain sectors and leading to expansion into new markets and demographic regions. One of the ways companies have stood out in recent decades is through their interest in environmental issues. In other words, people increasingly want to consume products and brands concerned with sustainability. The environmental labeling mechanism stands out, which is based on information available on packaging labels so that consumers choose to choose products with a lower environmental impact when compared to other products. In this context, the present research aims to verify the practices of conscious consumption in Juazeiro do Norte-CE, verifying if the consumers of supermarkets in the region have a purchase attitude influenced by the practice of socio-environmental responsibility. An opinion poll was applied to supermarket consumers in the city of Juazeiro do Norte. From the analysis of the results, it was possible to verify that despite the unsatisfactory results in relation to sustainability, more specifically the presence of environmental labels or certifications when buying something, most of them stated that they would stop using a brand or buy a product at the same time. knowing that a company or brand propagates positive environmental practices and, in fact, acts contrary to environmental interests and goods.